Vão-se os anéis, ficam-se os dedos: a educação da mocidade e a ilustração portuguesa nas obras de Luís Antonio Verney, Martinho de Pina de Proença e Antonio Nunes Ribeiro Sanches - Pimenta, Rodrigo Mello de Moraes (2015)
This work approaches the development of the Enlightenment and its meaning as a plural movement associated to the European varieties of “Modernities”. In order to corroborate this plurality, we analyzed the context of the so-called Portuguese Enlightened Modernity and its political set of ideas, both profoundly marked by the Counter-Reformation catholic thinking. Within this context, new discourses changed the aspect of the Portuguese political language and set of ideas, characterizing thus the intellectual effort to maintain the status quo that embodied the Portuguese Catholic Illustration. To confirm the happening of a Portuguese Catholic Illustration, the following works on the education in Portugal, published during the 18th century, were took as objects of analysis: Apontamentos sobre a Educação de hum menino nobre (1734), by Martinho de Mendonça de Pina e Proença, Verdadeiro método de estudar (1746), by father Luis Antônio Verney, and Cartas para Educação da mocidade (1760), by Antônio Nunes Ribeiro Sanches.